Tactical models of competitive activity of weightlifters - Мочернюк, В. Б. (Slobozhanskyi Herald of Science and Sport, 2011)
The purpose of the article is to research the peculiarities of the weightlifters’ competitive activity specificity in order to determine the optimal variants of tactical models for sportsmen of different weight categories among men and women. The statistical analysis of the score sheets of the largest international competitions for last years has been carried out. The indices of realisation based on the size depending of the make-weight in the competitive approaches have been determined. The results of researches give the opportunity to evaluate the probability of successful fulfilment of the assigned tasks and to choose an appropriate scheme of the performance.